2014
DOI: 10.1002/pbc.25318
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous B‐lymphoblastic lymphoma with IL3/IgH translocation presenting with hypereosinophilia and acute endocarditis

Abstract: Hypereosinophilia is a rare phenomenon associated with childhood malignancy, predominantly acute lymphoblastic leukaemia. Causation is unclear and likely to have multiple mechanisms. We report a six year old boy presenting with hypereosinophilia and associated Loeffler endocarditis. Three months following his initial hypereosinophilia he developed cutaneous B-lymphoblastic lymphoma. Re-analysis of apparently uninvolved bone marrow, taken at initial presentation, revealed a single, previously unidentified, t(5;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…It has been shown that hypereosinophilia heralds the onset and/or relapse of this particular subtype of ALL even in the absence of discernible clonal proliferation . These observations, including ours, suggest that the eosinophil counts can be a sensitive MRD barometer.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…It has been shown that hypereosinophilia heralds the onset and/or relapse of this particular subtype of ALL even in the absence of discernible clonal proliferation . These observations, including ours, suggest that the eosinophil counts can be a sensitive MRD barometer.…”
supporting
confidence: 68%
“…To the Editor: Acute lymphoblastic leukemia (ALL) with eosinophilia was first reported by Spitzer and Garson in 1973, and it was later classified as a distinct clinicopathological entity of B lymphoblastic leukemia/lymphoma with IL3‐IgH translocation in the revised WHO classification in 2008 . The chronological association between ALL and hypereosinophilia has been reported in the literature, but the exact molecular pathogenesis still remains uncertain.…”
mentioning
confidence: 99%
“…Cases of HE secondary to ALL are very rare. In addition to this child, only 61 patients <25 years (mean age 11 years) with HE and ALL have been described since 1973 to December 2017 ( Table 1 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested to combine IL-3 and G-CSF injection in peripheral blood for peripheral blood stem cell propagation and allogenic stem cell transplantation [ 45 , 46 ]. Recently, IL-3 hypersecretion has been reported to be associated with cutaneous B-lymphoblastic lymphoma [ 47 ]. Our study reveals another aspect of IL-3 functions, namely stimulating the stemness of prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%